Investigation and quantification of the potential antioxidant, inflammatory, and antibacterial bioactive molecules of the extracts of Algerian black and green table olive brine - Mohamadi,N; Meraghni, M; Meradci, F; Necib, A; El Arbi, M; Elhadef, K; Smaoui, S; Bouaziz, M. (My University, 2023)
table olive industry produces a large amount of wastewater that can be expensive to be treated and harmful to the environment. This study aimed to find a way to reuse brine water from the production of black and green table olive brines from Bejaia and Mascara of the Sigoise cultivar in order to create a valuable byproduct and contribute to sustainable development. In this context, the high-performance liquid chromatography–diode-array detection (HPLC-DAD) analysis revealed the highest concentration of hydroxytyrosol (4-(2-dihydroxy phenyl ethanol); 69.67 mg/100 mg) for green table olive brines of Mascara (EOGM) and tyrosol (Ty) (28.8 mg/100 mg) for black table olive brines of Bejaia (EOBB). Presence of polyphenols and ortho-diphenols could be responsible for their antioxidant, anti-inflammatory, and antibacterial properties. To assess antioxidant activity, the scavenging effects of DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,20-Azinobis[3-ethylbenzothiazoline-6-sulfonate]) radicals as well as hydrogen peroxide (H2O2) radicals were used. The antimicrobial activity showed that the black olive extract exhibited the best inhibitory effect, with a minimum inhibitory concentration (MIC) ranging from 0.625 mg/mL to 0.31 mg/mL. The anti-inflammatory activity of tested extracts of black olives of Bejaia (EOBB) and green of olives Mascara (EOGM) was 20.06 μg/mL and 20.21 μg/mL, respectively, which demonstrated the anti-inflammatory effect of these extracts on human beings.